Investigating the Impact of Social Media-Driven Sentiment on the Electric Vehicle Stock Market Using Quantile Regression - Çoban, Serap; Uçar, Mehmet; Ulusay, Nurten; Kaya, Nazife (International Journal of Economics and Financial Issues, 2025)
The electric vehicle (EV) sector has experienced remarkable growth, fueled by technological advancements, government incentives, and increasing environmental awareness. As the world shifts towards a low-carbon economy, EVs play a crucial role in reducing carbon emissions and shaping sustainable investment portfolios. This study investigates the impact of consumer sentiment on EV market performance, with a particular focus on social media platforms like Reddit. By constructing sentiment indices from user-generated content, the research applies quantile regression analysis to explore the relationship between social media-driven sentiment and sectoral stock returns. Unlike traditional models that focus on average market behavior, quantile regression captures the distributional effects of sentiment, particularly at the extremes, offering deeper insights into market volatility. The findings reveal how shifts in consumer sentiment, driven by emotional and behavioral factors, can significantly influence EV stock prices, providing valuable insights for investors and policymakers. This study contributes to the growing field of sustainable finance by introducing a novel approach to understanding how social media sentiment can guide investment decisions in the rapidly evolving EV sector, thereby supporting the transition to a more sustainable economy.